Usage of antidepressants in cancer patients - Matiiash, Taras; Bondarchuk, Andrii (Psychosomatic Medicine and General Practice, 2019)
Background: Approximately one million cancer patients live in Ukraine. These persons are at a high risk of manifestation of psychiatric disorders, especially depressive spectrum disorders and anxiety disorders, which may be treated with antidepressants if indications are present. Besides, oncological patients suffer from a number of miscellaneous somatic and psychosomatic conditions, that may also be totally or partly alleviated by using antidepressants. Thus, proper safe and evidence-based usage of these drugs is required. Unfortunately, there’s a lack of Ukrainian scientific literature highlighting this issue. This review is published to fulfill the aforementioned gap. Objectives: To survey the usage of antidepressants in the cohort of cancer patients, to evaluate a modern state of evidence base concerning this issue, and to study indications, contraindications, and other peculiarities in respect of prescribing these drugs to oncological patients. Methods: We reviewed and analyzed literature (meta-analyses, RTCs, observational studies, case studies) published in the last 10 years by searching PubMed and Google Scholar. We used the following keywords: “antidepressants”, “oncology”, “cancer”, “cancer symptoms”, “depression” and “drug interaction”. For our purposes, we also used NCCN, ASCO, ESMO, IPOS guidelines in case they were available and concerned our subject. Results: The review focuses attention on the usage of antidepressants in oncological patients. Best-practice recommendations for choosing a drug are given, information on a drug-to-drug interaction with chemotherapy and other common in oncology drugs, issues with regard to comorbid somatic problems that define prescribing, and off-label indications (pain, hot flushes, pruritus, etc.) are discussed. Conclusion: Despite the paucity of high-quality researches, a huge amount of evidences support the statement, that antidepressants significantly improve cancer patients’ quality of life by ceasing both depressive/anxious symptoms and typical cancer-related symptoms. To provide best professional help with these drugs, implementation of guidelines recommendations as well as adherence to experience collected from prescribing antidepressants to non-cancer population, which supports the effectiveness of this class of drugs for the treatment of depression, anxiety and pain are essential.